Isoprocarb induces acute toxicity in developing zebrafish embryos through vascular malformation - Hahyun Park; Gwonhwa Song; Whasun Lim (The Korean Society of Animal Reproduction and Biotechnology, 2021)
In this study, the potential toxicity of isoprocarb was demonstrated using zebrafish embryos. We treated isoprocarb (0, 29, and 58 mg/L) to the zebrafish embryos for 72 h then, we estimated morphological changes and apoptotic cell numbers. The increasing extent of apoptosis from the anterior to posterior region of developing zebrafish larvae was correlated with toxicity in the overall development process, including growth and normal organ formation. The appearance of abnormalities in the isoprocarb-treated groups in comparison to normal developing zebrafish larvae was verified using quantitative image analysis based on ImageJ software program. The vascular system comprising a complex interconnection of blood vessels was visualized in vessel-fluorescent transgenic zebrafish (fli1:eGFP). The main vasculature was malformed on isoprocarb treatment, and this was also related to cardiac defects. Taken together, normal embryonic development in zebrafish was interrupted owing to the acute toxicity of isoprocarb.